2022
DOI: 10.1038/s41419-022-05158-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FOXA2 induces ER stress and hepatic steatosis and alters developmental gene expression in human iPSC-derived hepatocytes

Abstract: FOXA2 has been known to play important roles in liver functions in rodents. However, its role in human hepatocytes is not fully understood. Recently, we generated FOXA2 mutant induced pluripotent stem cell (FOXA2−/−iPSC) lines and illustrated that loss of FOXA2 results in developmental defects in pancreatic islet cells. Here, we used FOXA2−/−iPSC lines to understand the role of FOXA2 on the development and function of human hepatocytes. Lack of FOXA2 resulted in significant alterations in the expression of key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Previous studies demonstrated that FOXA2 controls the expression of several TFs and genes involved in pancreatic endocrine cell fate and β-cell functionality [5,6]. Using human pluripotent stem cells (hPSCs), we and others reported that FOXA2 plays very important roles during human pancreatic and hepatic development [7][8][9]. A recent study reported that heterozygous missense variants in FOXA2 can lead to monogenic diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that FOXA2 controls the expression of several TFs and genes involved in pancreatic endocrine cell fate and β-cell functionality [5,6]. Using human pluripotent stem cells (hPSCs), we and others reported that FOXA2 plays very important roles during human pancreatic and hepatic development [7][8][9]. A recent study reported that heterozygous missense variants in FOXA2 can lead to monogenic diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic progenitors and mature hepatocytes differentiated by FOXA2 mutant induced pluripotent stem cells (FOXA2 -/- IPSC) exhibited increased expression of endoplasmic reticulum stress markers. Mature hepatocytes showed increased lipid accumulation and overcame lipid accumulation and the resulting toxicity through increased levels of free glycerol and CYP3A4 ( 97 ).…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…FOXA2 is an important transcription factor essential in the growth and development of liver. Studies reported that ERS induced by FOXA2 knockdown in hepatocytes could cause cholestasis and bile acid toxicity, increase lipid accumulation in hepatocytes and cause hepatic steatosis [ 68 , 69 ]. Interestingly, it has been documented that FOXA3 exerts opposite effects to FOXA2.…”
Section: The Important Role Of Endoplasmic Reticulum Stress In Liver ...mentioning
confidence: 99%
“… [ 65 67 ] KO FOXA2 (−) iPSC-derived hepatocytes and Cre mice Activating ERS, causing hepatic steatosis, bile acid toxicity. [ 68 , 69 ] HFD/TM FOXA3 (−) Mice Alleviating ERS, reducing lipid accumulation and preventing hepatic steatosis. [ 70 ] TM XBP1 (−) C57BL/6 mice Exacerbating ERS, inducing hepatocyte death and progression of liver fibrosis, and progressively aggravating liver injury.…”
Section: The Important Role Of Endoplasmic Reticulum Stress In Liver ...mentioning
confidence: 99%